Liposome-Encapsulated Morphine Affords a Prolonged Analgesia While Facilitating Extinction of Reward and Aversive Memories - Gómez-Murcia, Victoria; Ribeiro Do Couto, Bruno; Gómez-Fernández, Juan C.; Milanés, María V.; Laorden, María L.; Almela, Pilar (Frontiers in Pharmacology, 2019)
Morphine, as other opiates, is widely used for pain relief, however, it has a high addictive potential. Opioid liposome formulations produce controlled drug release and have been thoroughly tested for pain treatment although their role in addiction is still unknown. This study investigated the effects of free-morphine and morphine encapsulated in unilamellar and multilamellar liposomes on antinociception and on the expression and extinction of the positive and negative memories associated with environmental cues. The hot plate test was used to evaluate central pain. The rewarding effects of morphine were evaluated using the conditioned place preference (CPP) paradigm, and the negative state associated with naloxone-precipitated morphine withdrawal was examined by the conditioned place aversion (CPA) test. Our results show that encapsulated morphine yields prolonged antinociceptive effects compared with the free form, and that CPP and CPA expression were similar in the free- or encapsulated-morphine groups. However, we demonstrate, for the first time, that morphine encapsulation reduces the duration of reward and aversive memories, suggesting that this technological process could transform morphine into a potentially less addictive drug. Morphine encapsulation in liposomes could represent a pharmacological approach for enhancing extinction, which might lead to effective clinical treatments in drug addiction with less side effects.